Experimental and numerical study of anisotropic thermal conductivity of magnetically aligned PDMS/Ni particle composites. (June 2016) - Su, Junwei; Liu, Xiao; Charmchi, Majid; Sun, Hongwei
Highlights: Magnetically aligned PDMS/Ni particle composites were fabricated to enhance the anisotropic thermal conductivity. The effect of volume fractions on the morphology of Ni column structures was clarified. A reusable 3-omega technologies was applied for measuring the thermal conductivity of PDMS/Ni composites. A finite element numerical modeling (FEM) was used to predict the thermal conductivity improvement of PDMS/Ni composites. Abstract: In this research, Polydimethylsiloxane (PDMS)/nickel (Ni) composites with embedded Ni spherical particle columns were studied for thermal conductivity enhancement. The volume fraction of Ni particles ranged from 2% to 20% while the strength of the applied magnetic field was fixed at 0.45 Tesla. The distribution and morphology of the column structures were quantitatively analyzed using optical microscope, Scanning Electron Microscope (SEM) and digital image processing. A reusable 3ω measurement technique was applied to measure the effective thermal conductivity of PDMS/Ni composites in the parallel direction to the magnetic field. The measured thermal conductivity was compared with the prediction from a finite element model built on the observed microscopic structures. Under a static magnetic field, Ni particles align parallel to the field forming columns. The results illustrated that the diameter of Ni columns increased with increasing particle volume fraction while the center to center spacing between columns did not change substantially under the fixed magnetic strength. The magnetically aligned particle columns significantly enhanced the thermal conductivity of PDMS compared to the randomly distributed particles by about two fold. However, the point contacts between magnetically aligned spherical fillers are the major limiting factor for the further improvement of thermal conductivity.